ANALYZING HOW URBANIZATION IMPACTS ECONOMIC GROWTH IN NIGERIA - Ahmed Oluwatobi Adekunle (J-MACC, 2024)
Research on the complex interplay among urbanization and economic growth frequently examines a number of factors, including industrial sectors including manufacturing, high-tech industries, and productive service industries missing aggregate analysis. Sequel to this, this study analyzed how urbanization impacts economic growth in Nigeria. Essentially, the study uses unit root testing, vector error correction model (VECM) and causality method to analyze the data span over 1986-2021. Given that the likelihood is negligible at 0.39%, the null hypothesis—that there is no causal association between jobs and economic development, directed from jobs to economic growth—cannot be rejected at 5%. On the other hand, at 5%, the null hypothesis—that there is no causal relationship between CGDP and employment—can be rejected, with a probability of 0.02%, which is highly significant. Therefore, for the time span covered by the analysis, there is a unidirectional causal relationship in Nigeria between jobs and economic growth, with jobs driving economic expansion. indicating that more jobs can be created in Nigeria as a result of increased economic growth. The use of the empirical framework and data restrictions are two of the study's shortcomings. To further explore this empirical issue, future efforts should concentrate more on the study of panel and quarterly data.